Silicon-carbon anode composite binder, anode sheet, lithium-ion battery and preparation method
Patent Information
- Application Number
- CN202611423799.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-20
AI Technical Summary
[0011]针对现有技术的不足,本发明的目的在于提供一种硅碳负极复合粘结剂及其负极极片和锂离子电池,以及锂离子电池的制备方法,以解决硅碳负极在充放电过程中因巨大体积膨胀导致的颗粒粉化、粘结脱附、导电网络断裂和循环寿命缩短等问题
1、弹性缓冲与结构支撑的协同统一:特种聚氨酯软硬段微相分离的结构特征使其兼具高弹性和高强度。软段(聚醚/聚酯多元醇)分子链柔顺、可自由卷曲伸展,断裂伸长率高(可达数百甚至上千百分比),当硅碳颗粒嵌锂膨胀时,软段如同弹簧一样伸展,吸收和分散体积膨胀产生的应力,有效缓解界面应力集中;硬段(二异氰酸酯+扩链剂)通过氢键聚集形成微相区,作为物理交联点分散在软段基体中,在提供结构支撑力的同时维持极片整体完整性。这种刚柔并济的结构是单一PAA或SBR粘结剂无法实现的——PAA成膜偏硬、脆性较高,SBR虽弹性好但缺乏界面锚固能力。本发明通过聚氨酯的软硬段协同,从根本上解决了弹性缓冲与结构强度之间的矛盾。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a silicon-carbon anode composite binder, anode sheet, lithium-ion battery, and preparation method. The composite binder is particularly suitable for lithium-ion battery anode systems containing silicon-carbon active materials, and can buffer the volume deformation of silicon-carbon materials during charging and discharging, maintain the stability of the electrode conductive network, and improve battery cycle life and safety. Background Technology
[0002] With the increasing demands for longer battery life in consumer electronics and the urgent need for higher energy density in electric vehicles and energy storage systems, improving the volumetric energy density of batteries—that is, increasing battery capacity within a limited volume—has become one of the core directions for the development of lithium-ion battery technology. In recent years, doping silicon-based anode materials into the anode system of battery raw materials can significantly improve battery capacity and energy density, becoming a research hotspot and a key focus of industrialization.
[0003] Silicon (Si) has a theoretical specific capacity of approximately 4200 mAh / g (based on elemental silicon), far exceeding the approximately 372 mAh / g of traditional graphite anodes (graphite in a full cell is approximately 340–360 mAh / g). Currently, silicon-carbon composite materials produced using chemical vapor deposition (CVD) can achieve a full-cell specific capacity of approximately 1800 mAh / g, more than five times that of graphite anodes. Therefore, incorporating silicon-carbon composite materials into graphite anodes can significantly improve the overall capacity of the battery cell.
[0004] However, the chemical structure of silicon-based anode materials (mainly referring to silicon-carbon composites, Si / C) determines that they suffer from severe volume effects during lithium insertion / extraction during charge and discharge. Specifically, silicon forms a lithium-silicon alloy (Li₂) with lithium during lithium insertion. x Si, accompanied by a huge volume expansion (approaching 300%), undergoes volume contraction during delithiation. This drastic and repeated volume change can trigger a series of cascading failure problems, mainly including: (1) Silicon carbon particles pulverize, crack, or even break off during repeated expansion and contraction, resulting in the loss of electrical contact of active materials; (2) The adhesive system cannot withstand such large deformation stress, resulting in adhesive desorption, breakage of the conductive network, formation of isolated areas, and a sharp decrease in the overall conductivity of the electrode. (3) The repeated rupture and regeneration of the SEI (solid electrolyte interface) membrane continuously consumes electrolyte and active lithium, leading to a decrease in coulombic efficiency and capacity decay. (4) Excessive overall expansion rate of the electrode leads to powder shedding from the negative electrode, shortens the battery cycle life, and increases safety hazards.
[0005] To address the aforementioned expansion problem, the following adhesive systems are primarily used in existing technologies: (I) Traditional graphite formulation: active material (graphite) + conductive agent + CMC + SBR. CMC (sodium carboxymethyl cellulose) acts as a dispersant and thickener, while SBR (styrene-butadiene rubber) provides elasticity and flexibility. This system performs well in graphite anodes, with mature technology and low cost. However, SBR mainly relies on point-to-point physical adhesion between particles, lacking chemical bonding with the active material. When faced with the 300% volume expansion of silicon-carbon anodes, the elastic deformation capacity of SBR is far from sufficient, easily leading to adhesion / desorption and electrode cracking. CMC itself forms a relatively hard and brittle film, contributing limited to structural stability. Therefore, the CMC+SBR system is difficult to apply to anode systems with high silicon content.
[0006] (II) Existing Silicon-Carbon Formulation: Active Material (Graphite + Silicon-Carbon) + Conductive Agent + PAA + CMC + SBR. Polyacrylic acid (PAA) molecules contain a large number of carboxyl groups (-COOH), which can form hydrogen bonds or even chemical bonds with the hydroxyl groups (-OH) on the silicon surface. Compared with traditional physical adhesion methods, its interfacial bonding is stronger. PAA binds particles through its linear structure, resulting in higher particle anchoring and stronger cohesion within the electrode, which is beneficial to structural stability. PAA is one of the most widely used binders in current silicon-based anodes and can, to a certain extent, suppress silicon-carbon expansion.
[0007] However, the existing PAA system still has the following shortcomings: (1) PAA films are relatively hard and brittle. When used alone, they are prone to cracking after drying. Especially during repeated expansion-contraction cycles, although PAA linear segments have a certain spring effect, their elastic recovery ability and elongation at break are limited, making it difficult to fully match the volume change of silicon-carbon materials, which can reach up to 300%. (2) Although the PAA+CMC+SBR ternary system improves flexibility through SBR, the adhesion of SBR mainly depends on physical action and lacks strong anchoring ability for active materials. Furthermore, the unsaturated carbon-carbon double bond of SBR may undergo side reactions in the electrochemical environment, affecting long-term stability. (3) In high silicon content (silicon-carbon ratio >10%) or all silicon-carbon anode systems, the existing binder system has insufficient structural maintenance ability, and there is still considerable room for improvement in cycle life and safety.
[0008] In recent years, polyurethane (PU) materials have attracted much attention due to their block structure with coexisting hard and soft segments. The main chain of a polyurethane molecule contains a large number of repeating urethane groups (-NH-COO-), with diisocyanates and chain extenders forming the hard segment regions, and long-chain polyethers / polyester polyols forming the soft segment regions. The hard segments are highly rigid, forming numerous hydrogen bonds between molecules, resulting in tight packing and imparting strong adhesion, cohesive force, and structural support to the material. The soft segment molecular chains are flexible, with high elongation at break, exhibiting excellent elasticity and deformation recovery. The hard segments aggregate due to hydrogen bonding to form microphase regions, dispersed within a continuous soft segment matrix, creating a microphase-separated structure that allows polyurethane to simultaneously possess both high-strength adhesive properties and high elastic deformation capacity.
[0009] However, the application of polyurethane in silicon-carbon anodes is still in the exploratory stage, with problems such as insufficient electrochemical stability, system complexity, and high cost, and a mature industrial solution has not yet been formed. In particular, there are still technological gaps in how to synergize with existing PAA systems and how to achieve an organic unity of elastic buffering and interfacial anchoring at the molecular level.
[0010] In summary, the existing technology lacks a composite adhesive system that can fully utilize the high elasticity and buffering advantages of polyurethane and synergistically enhance interfacial adhesion with PAA to solve the problems of pulverization, powder shedding, and structural collapse caused by the volume expansion of silicon-carbon anodes. Summary of the Invention
[0011] In view of the shortcomings of the prior art, the purpose of this invention is to provide a silicon-carbon anode composite binder, its anode sheet and lithium-ion battery, as well as a method for preparing the lithium-ion battery, so as to solve the problems of particle pulverization, bond desorption, conductive network breakage and shortened cycle life caused by the huge volume expansion of silicon-carbon anodes during charging and discharging.
[0012] The technical solution adopted in this invention is a silicon-carbon anode composite binder, which includes a special polyurethane and polyacrylic acid; The special polyurethane has a large number of repeating urethane groups (-NH-COO-) on its molecular backbone, and the overall molecular chain exhibits a special block structure with soft and hard segments separated into microphases. The hard segment is composed of urethane segments formed by the reaction of aromatic or aliphatic diisocyanates with small molecule chain extenders, with a large number of hydrogen bonds forming between molecules. The soft segment is a long-chain flexible macromolecular chain of polyether or polyester. Hard segments aggregate with each other due to hydrogen bonding to form microphase regions, which are dispersed in a continuous soft segment matrix, forming a microphase-separated structure.
[0013] Furthermore, the soft segment of the special polyurethane is a polyether polyol or a polyester polyol, wherein the polyether polyol is selected from one or more of polyethylene oxide ether, polypropylene oxide ether, and polytetrahydrofuran ether; and the polyester polyol is selected from one or more of polyethylene adipate, polybutylene adipate, and polycarbonate polyol.
[0014] Further, the diisocyanate is selected from one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI); the chain extender is selected from one or more of ethylene glycol, 1,4-butanediol, 1,6-hexanediol, ethylenediamine, and diaminodiphenylmethane.
[0015] Furthermore, the mass ratio of the special polyurethane to PAA is 1:10 to 10:1; preferably 1:5 to 5:1.
[0016] Furthermore, the special polyurethane is an aqueous polyurethane, with water as the dispersion medium; the polyacrylic acid is an aqueous polyacrylic acid emulsion or aqueous solution.
[0017] A negative electrode sheet, comprising a current collector and a negative electrode active layer coated on the surface of the current collector, wherein the raw materials for preparing the negative electrode active layer include: Active materials, including graphite and silicon-carbon composites; Conductive agents; and The composite adhesive as described above; The special polyurethane in the composite binder buffers the volume expansion of silicon carbon particles during charging and discharging through the elastic deformation of its soft segments, maintains the integrity of the electrode structure through hydrogen bonding aggregation in its hard segment microphase region, and enhances interfacial adhesion through hydrogen bonding between its polar urethane groups and the surface of the active material and the current collector.
[0018] Furthermore, the raw material composition for preparing the negative electrode active layer, by mass percentage, is as follows: Active material: 85%–97%, conductive agent: 1%–8%, composite binder: 2%–7%; The total mass of the composite adhesive is the sum of the special polyurethane and polyacrylic acid, with the special polyurethane accounting for 10% to 90% of the total mass of the adhesive.
[0019] Furthermore, the silicon-carbon composite material is prepared by chemical vapor deposition, and the total specific capacity of the silicon-carbon composite material is 1000-1800 mAh / g; the total specific capacity of the graphite is 340-360 mAh / g.
[0020] A lithium-ion battery includes a positive electrode, a separator, an electrolyte, and a negative electrode as described above.
[0021] A method for preparing a lithium-ion battery as described above, the method comprising the following steps: S1. Active material, conductive agent, special polyurethane and polyacrylic acid are added to deionized water and mixed into a slurry to obtain a uniformly dispersed negative electrode slurry; wherein, the special polyurethane and polyacrylic acid form an interpenetrating network structure in the slurry. S2. The negative electrode slurry is coated onto the surface of the copper foil current collector to form a wet coating. S3. Dry the coated electrode to remove solvent and moisture, so that the special polyurethane and polyacrylic acid can be cured together to form a bonding network between the active materials. S4. Roller-press the dried electrode sheets to control the porosity of the electrode sheets; S5, the rolled electrode sheet is cut and assembled with the positive electrode sheet and separator, and then the lithium-ion battery is obtained after encapsulation and liquid injection; During the charge-discharge cycle, the soft segments of the special polyurethane undergo elastic stretching to buffer the volume expansion stress of the silicon carbon particles, while the hard segment microphase region serves as a physical crosslinking point to maintain the integrity of the electrode structure. Polyacrylic acid forms hydrogen bonds and chemical bonds with the surface of silicon carbon particles through its carboxyl groups, thereby achieving interface anchoring.
[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. Synergistic Unity of Elastic Buffering and Structural Support: The microphase separation structure of the soft and hard segments in special polyurethane endows it with both high elasticity and high strength. The soft segments (polyether / polyester polyol) have flexible molecular chains that can freely coil and extend, with high elongation at break (up to hundreds or even thousands of percent). When silicon-carbon particles expand due to lithium intercalation, the soft segments extend like springs, absorbing and dispersing the stress generated by volume expansion, effectively alleviating interfacial stress concentration. The hard segments (diisocyanate + chain extender) aggregate through hydrogen bonding to form microphase regions, which act as physical crosslinking points dispersed in the soft segment matrix, providing structural support while maintaining the overall integrity of the electrode. This combination of rigidity and flexibility cannot be achieved by a single PAA or SBR binder—PAA films are relatively hard and brittle, while SBR, although elastic, lacks interfacial anchoring ability. This invention fundamentally solves the contradiction between elastic buffering and structural strength through the synergistic effect of the soft and hard segments of polyurethane.
[0023] 2. Polar groups enhance interfacial adhesion and maintain the stability of the conductive network: The special polyurethane molecular chain contains a large number of polar urethane groups (-NH-COO-), in which the carbonyl oxygen and amino hydrogen can form multiple hydrogen bonds with the oxygen-containing functional groups (such as Si-O, C=O, etc.) on the surface of silicon-carbon particles and the surface of copper foil current collectors. The strength of hydrogen bonds (approximately 10-40 kJ / mol) is much higher than that of van der Waals forces (approximately 0.4-4 kJ / mol). Therefore, the interfacial adhesion between polyurethane and the active material and current collector is significantly better than the physical adsorption of traditional SBRs. During repeated expansion-contraction cycles, strong hydrogen bonding can effectively prevent adhesion and desorption and active material shedding, maintain the continuity of the electrode conductive network, thereby ensuring unobstructed electron transport channels and improving battery cycle stability.
[0024] 3. Synergistic effect of polyurethane and PAA for multi-layered bonding: This invention combines a special polyurethane with PAA, forming an interpenetrating network structure in the slurry and exerting a synergistic effect: the carboxyl groups of PAA form hydrogen bonds or even chemical bonds (such as esterification or ionic bonds) with the hydroxyl groups on the surface of silicon-carbon particles, providing microscopic anchoring; the soft segment elastic network of polyurethane wraps the entire electrode structure, providing macroscopic buffering. The synergistic effect of the two covers multi-layered stress management from single particles to the entire electrode sheet—PAA firmly anchors the active material at the particle scale, while polyurethane buffers overall deformation at the electrode scale. This synergistic effect cannot be achieved by simply replacing the binder (such as replacing SBR with only PU), because this invention utilizes the complementarity of the two binders in molecular structure and mechanism of action.
[0025] 4. Highly adjustable and adaptable to different silicon-carbon contents: The technical solution of this invention has excellent adjustability. By adjusting the ratio of soft and hard segments, the type of polyol, and the isocyanate structure, the elasticity, modulus, electrolyte resistance, and adhesive strength of the polyurethane can be precisely controlled; by adjusting the mass ratio of polyurethane to PAA, the elastic buffering capacity and interfacial anchoring strength can be balanced. For example, in a high-silicon content system, the proportion of polyurethane can be appropriately increased to enhance elastic buffering, while in a low-silicon content system, the proportion of PAA can be increased to reduce costs. This flexible formulation capability allows this invention to be adapted to a wide range of applications, from low-silicon doping (silicon-carbon ratio 5%–10%) to high-silicon systems (silicon-carbon ratio >15%).
[0026] 5. Improved Battery Energy Density, Cycle Life, and Safety: Through the combined effects of elastic buffering, interface enhancement, and synergistic bonding, this invention effectively suppresses the volume expansion and particle pulverization of the silicon-carbon anode, preventing anode powder shedding and maintaining the integrity of the electrode structure and the stability of the conductive network. This enables the stable application of high-capacity silicon-carbon materials in practical batteries—fully utilizing the high capacity advantage of silicon-carbon (approximately 1800 mAh / g, about 5 times higher than graphite's 340–360 mAh / g), while avoiding cycle degradation and safety hazards caused by uncontrolled expansion. From the perspective of the overall battery, this invention improves energy density, extends cycle life, reduces the risk of thermal runaway, and achieves a comprehensive improvement in capacity, lifespan, and safety.
[0027] 6. Experimentally verified expansion suppression and cycle improvement effects: As shown in Examples 5-7 and Comparative Examples 1-2 of the specific implementation methods, at an 8% silicon-carbon content, the composite binder system of the present invention, compared with the traditional PAA+CMC+SBR system, reduced the electrode expansion rate from 31.2% to 14.5% after 300 cycles, increased the capacity retention rate from 82.4% to 91.3%, and increased the peel strength from 26 N / m to 42 N / m. This effect is not solely achieved through the hydrogen bond anchoring of PAA, but rather through the synergistic effect of the elastic buffering of polyurethane soft segments, the physical cross-linking of hard segments, and the interfacial anchoring of PAA carboxyl groups. When silicon-carbon particles expand due to lithium intercalation, the polyurethane soft segments first undergo elastic stretching to absorb stress, preventing stress concentration at the particle / binder interface. When the soft segments stretch to a certain extent, the microphase region of the hard segments acts as a physical cross-linking point to limit further deformation, preventing the overall electrode from expanding uncontrollably. At the same time, the hydrogen bonds / chemical bonds formed by the carboxyl groups of PAA and the hydroxyl groups on the silicon-carbon surface continuously provide interfacial anchoring. The three factors form a multi-level stress dissipation path from a single particle to the entire electrode.
[0028] 7. Electrolyte stability: The special polyurethane used in this invention has a mass swelling rate of about 28.9% and a thickness swelling rate of about 5.6% after being stored in an electrolyte at 60°C for 7 days. It did not dissolve or break down, proving that it can maintain its structural integrity for a long time in the actual chemical environment of the battery cell and will not lose its bonding function due to electrolyte erosion. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the silicon-carbon negative electrode sheet structure containing a special polyurethane composite binder according to the present invention; Figure 2 This is a schematic diagram of the soft and hard segment block structure of the special polyurethane of the present invention and its microphase separation and volume buffering mechanism. Figure 3 This is a flowchart illustrating the manufacturing process of the lithium-ion battery described in this invention. Detailed Implementation
[0030] Preparation Examples of Specialty Polyurethanes: To enable those skilled in the art to implement this invention, the specific synthesis routes and parameters for specialty polyurethanes are given below. The specialty polyurethanes described in this invention can be synthesized using a prepolymer method or a one-step method, with the prepolymer method being preferred to obtain a more regular soft-hard segment block structure.
[0031] Synthetic route (prepolymer method): (a) Preparation of prepolymer: Under dry nitrogen protection, polyether polyol or polyester polyol (number average molecular weight M_n of 1000-4000 g / mol, preferably 2000 g / mol) is vacuum dehydrated at 100-120°C for 1-2 hours; the temperature is lowered to 60-80°C, and diisocyanate (one or more of TDI, MDI, IPDI or HDI) is added, the NCO / OH molar ratio is controlled at 1.8-2.2, and the reaction is carried out at 70-85°C for 1.5-3 hours to obtain terminal-NCO prepolymer.
[0032] (b) Chain extension and neutralization: The prepolymer is cooled to 40-60°C, and a small molecule chain extender (one or more of ethylene glycol, 1,4-butanediol, 1,6-hexanediol, ethylenediamine or diaminodiphenylmethane) is added. The chain extension reaction is carried out for 20-60 minutes. Then, when the hydrophilic chain extender dimethylolpropionic acid (DMPA) is added, the carboxyl group is neutralized with the neutralizing agent triethylamine to obtain an aqueous polyurethane dispersion.
[0033] (c) Dispersion: The reaction product is slowly added to deionized water under high-speed shear (3000-8000 rpm) to emulsify and disperse, and an aqueous polyurethane dispersion is obtained. The solid content is controlled at 20%-40wt%, preferably 30wt.
[0034] By adjusting the isocyanate index (total molar ratio of NCO / OH) within the range of 0.95 to 1.05, the molecular weight and degree of crosslinking of polyurethane can be controlled. When NCO / OH = 1.0, it has a linear structure and the best elasticity. When NCO / OH is slightly greater than 1.0, there are a small number of unreacted NCO groups, which can form mild crosslinking with PAA carboxyl groups or hydroxyl groups on the surface of active substances.
[0035] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.
[0036] Example 1
[0037] This embodiment provides a method for preparing a silicon-carbon anode composite binder and its anode sheet.
[0038] (1) Composition of composite adhesive: Specialty polyurethane: Waterborne polyether polyurethane (soft segment is polyoxypropylene ether, hard segment is formed by chain extension of isophorone diisocyanate IPDI and 1,4-butanediol), solid content is about 30 wt%, molecular weight is about 5 × 10⁻⁶ 4 ~2×10 5 g / mol. The polyurethane soft segment provides elastic cushioning, while the hard segment provides structural support and interfacial adhesion.
[0039] PAA: Water-based polyacrylic acid emulsion with a solid content of approximately 15 wt% and a molecular weight of approximately 10. 5 g / mol. The carboxyl groups of PAA form hydrogen bonds and chemical bonds with the surface of silicon-carbon particles, providing interfacial anchoring.
[0040] The mass ratio of specialty polyurethane to PAA is 1:1 (i.e., each accounts for 50% of the total mass of the adhesive). The two have good compatibility in the water-based system and form an interpenetrating network structure.
[0041] (2) Preparation of negative electrode slurry (mixing slurry): Weigh each component according to the following mass percentage ratio: Active material: graphite (artificial graphite, D50≈15μm) + silicon-carbon composite material (prepared by CVD process, Si / C mass ratio approximately 1:1, full cell specific capacity approximately 1500mAh / g), of which silicon-carbon accounts for 8% of the total mass of the active material. The total mass of graphite and silicon-carbon is 90.5%.
[0042] Conductive agent: conductive carbon black (Super P) + carbon nanotubes (CNT), with a total mass of 2.5%.
[0043] Composite adhesive: Special polyurethane + PAA, total mass 7%. Polyurethane accounts for 3.5% and PAA accounts for 3.5%.
[0044] The active material, conductive agent, special polyurethane, and PAA were added to deionized water and mixed in a vacuum mixer (30 Hz revolution, 50 Hz rotation, approximately 2 hours) to obtain a uniformly dispersed negative electrode slurry. The slurry viscosity was controlled at 3000–6000 mPa·s (25℃).
[0045] During this process, the specialty polyurethane and PAA are thoroughly mixed in an aqueous medium. Hydrogen bonds can form between the polar urethane groups of the polyurethane and the carboxyl groups of the PAA, and the two polymer segments interpenetrate each other, initially forming an interpenetrating network structure. This interpenetrating network is further strengthened after subsequent drying and curing, forming a composite adhesive network that combines elasticity (contributed by polyurethane) and strong adhesion (contributed by PAA).
[0046] (3) Coating: The above negative electrode slurry is coated on the surface of the copper foil current collector (thickness about 8 μm) at a coating speed of about 2 to 5 m / min and the wet coating thickness is about 150 to 200 μm.
[0047] (4) Drying: Place the coated electrode in an oven and dry it at 80-120℃ for about 2-4 hours to remove moisture and solvent. During the drying process, polyurethane and PAA are cured synergistically to form a three-dimensional bonding network between the active materials.
[0048] (5) Roller pressing: The dried electrode sheets are compacted using a roller press, and the compaction density of the electrode sheets is controlled to be approximately 1.5–1.7 g / cm³. 3 The porosity is approximately 25% to 35%.
[0049] (6) Cutting and assembly: The rolled electrode sheets are cut to the required size and stacked or wound together with the positive electrode sheet (such as NCM811) and the separator (polyethylene / polypropylene composite separator). After aluminum-plastic film encapsulation, electrolyte injection (LiPF6 / EC+DEC+DMC), and formation, a soft-pack lithium-ion battery is obtained.
[0050] Example 2
[0051] The main difference between this embodiment and Embodiment 1 lies in the silicon-carbon content and the ratio of the composite binder; the rest of the preparation process is the same.
[0052] In this example, the silicon-carbon composite material accounts for 15% of the total mass of the active material (higher than 8% in Example 1), and the corresponding graphite content is reduced. Due to the increased silicon-carbon content, the volume expansion effect is more significant. Therefore, the mass ratio of special polyurethane to PAA in the composite binder is adjusted to 2:1 (polyurethane accounts for approximately 67% of the total mass of the binder, and PAA accounts for approximately 33%) to enhance the elastic cushioning capacity.
[0053] Specifically, the negative electrode active layer composition is as follows: 90.0% active material (graphite + silicon carbide), 2.5% conductive agent, and 7.5% composite binder (of which 5.0% is polyurethane and 2.5% is PAA).
[0054] The principle behind this formulation is that when the silicon-carbon content is high, the volume expansion is more dramatic, requiring more elastic buffer components to absorb and disperse stress. The elastic deformation capability of polyurethane soft segments is far superior to that of PAA linear segments; therefore, appropriately increasing the polyurethane proportion helps to better match the volume changes of the high-silicon system. At the same time, a certain amount of PAA (not less than 25%) is retained to ensure sufficient interfacial anchoring strength and prevent a decrease in adhesion due to an excessively high polyurethane proportion.
[0055] Example 3
[0056] The main difference between this embodiment and Embodiment 1 lies in the hard segment structure of the polyurethane; the rest of the preparation process and proportions are basically the same.
[0057] In this embodiment, the hard segment of the special polyurethane is formed by reacting an aromatic diisocyanate—toluene diisocyanate (TDI)—with a chain extender, while the soft segment remains polyoxypropylene ether. The urethane bonds formed by aromatic isocyanates have higher rigidity and stronger hydrogen bonding, resulting in a higher physical crosslinking density in the hard segment microphase region and better modulus and heat resistance of the material.
[0058] Meanwhile, polytetrahydrofuran ether (PTMEG) is used instead of polypropylene oxide ether (PPG) for the soft segment. PTMEG has better flexibility than PPG, and its soft segment has a lower glass transition temperature (Tg), which can maintain good elasticity at low temperatures, thus improving the cycle stability of the battery over a wide temperature range.
[0059] By adjusting the isocyanate index (NCO / OH molar ratio) within the range of 0.95 to 1.05, the molecular weight and degree of crosslinking of polyurethane can be controlled. When NCO / OH = 1.0, the polyurethane has a linear structure with optimal elasticity but slightly weaker cohesion. When NCO / OH is slightly greater than 1.0, a small amount of unreacted NCO groups exist, which can undergo side reactions with the carboxyl groups of PAA or the surface hydroxyl groups of active substances, forming mild crosslinking and further improving cohesive strength. An NCO / OH ratio of 1.0 to 1.02 is preferred.
[0060] Example 4 (Specific Synthesis Example of Special Polyurethane) This embodiment provides the specific synthesis process of the special polyurethane used in Embodiment 1 of the present invention.
[0061] 100 parts by weight of polyoxypropylene ether diol (PPG, M_n≈2000 g / mol) were dehydrated under vacuum at 110℃ for 1.5 hours; the temperature was then lowered to 75℃, and 18.5 parts by weight of IPDI (NCO / OH molar ratio≈2.0) were added. The mixture was reacted at 80℃ for 2 hours to obtain an end-NCO prepolymer. The prepolymer was cooled to 50℃, and 6.2 parts by weight of 1,4-butanediol were added for chain extension, reacting for 30 minutes; subsequently, 3.0 parts by weight of DMPA were added, and neutralized with 2.2 parts by weight of triethylamine to obtain a carboxyl-containing polyurethane prepolymer. The product was slowly added to deionized water under high-speed shear at 5000 rpm for emulsification and dispersion, and the solid content was adjusted to 30 wt% to obtain an aqueous polyether-type polyurethane dispersion with a molecular weight of approximately 8 × 10⁻⁶. 4 g / mol.
[0062] The polyurethane soft segment is polyoxypropylene ether, and the hard segment is composed of urethane segments formed by the reaction of IPDI and 1,4-butanediol. The hard segment aggregates due to hydrogen bonding to form microphase regions, which are dispersed in the continuous soft segment matrix, exhibiting a microphase separation structure.
[0063] Examples 5-7 and Comparative Examples 1-2 (Verification Experiments) To verify the technical effect of the present invention, the following provides a comparison of electrode performance under different silicon-carbon contents and different polyurethane / PAA mass ratios, as well as comparative data.
[0064] Battery assembly and testing conditions (the same as those in Examples 5-7 and comparative examples below): Positive electrode: NCM811, with a positive active material layer thickness of approximately 60 μm; Separator: Polyethylene / polypropylene composite diaphragm, approximately 12 μm thick; Electrolyte: 1 mol / L LiPF6, solvent is EC:DEC:DMC=1:1:1 (volume ratio), with 5 wt% FEC added; The N / P ratio should be controlled between 1.05 and 1.15. Negative electrode sheet: Prepared according to the methods in Examples 1-4, with a copper foil thickness of 8 μm, a negative electrode active layer thickness of approximately 70 μm, and a compaction density of 1.5-1.7 g / cm³. 3 ; Packaging: Aluminum-plastic film soft package, designed capacity approximately 120mAh; Formation: Charge to 3.0V at 0.05C, charge to 4.2V at 0.1C, and maintain constant voltage until cutoff at 0.05C; Cyclic test: 25±2℃, constant current charging at 0.5C to 4.2V, constant voltage charging at 0.05C, resting for 5 minutes, and discharging at 0.5C to 2.8V constitutes one cycle; Electrode expansion rate test: After 100 and 300 cycles, the battery was disassembled and the thickness H_n of the negative electrode active layer was measured with a micrometer. The expansion rate = (H_n-H_0) / (H_0-H_Cu)×100%, where H_0 is the thickness of the electrode after rolling and H_Cu is the thickness of the copper foil. Peel strength: The negative electrode sheet was cut into 20mm wide strips and a 180° peel test was performed at a speed of 50mm / min. The average peel force (N / m) was recorded. First-time efficiency: First charge / discharge efficiency = First discharge capacity / First charge capacity × 100%.
[0065] The formulation and results are shown in Table 1.
[0066] Table 1. Comparison of negative electrode formulations and performance of different binder systems Example 5 8% 1:1 7% 8.2% 14.5% 91.3% 42 89.5% Example 6 10% 1:1 7% 9.1% 16.8% 89.7% 40 88.9% Example 7 15% 2:1 7.5% 11.3% 20.4% 87.1% 38 87.6% Comparative Example 1 8% - (PAA+CMC+SBR) PAA 4% + CMC 1.5% + SBR 1.5% 15.6% 31.2% 82.4% 26 86.1% Comparative Example 2 15% - (PAA+CMC+SBR) PAA 4% + CMC 1.5% + SBR 1.5% 21.8% 44.7% 73.8% 19 84.3% As shown in Table 1, under the same silicon-carbon content (8%), compared with the traditional PAA+CMC+SBR system (Comparative Example 1), the expansion rate after 300 cycles of the present invention (Example 5) decreased from 31.2% to 14.5%, a reduction of approximately 53%; the capacity retention rate after 300 cycles increased from 82.4% to 91.3%; and the peel strength increased from 26 N / m to 42 N / m. The principle is that the polyurethane soft segments elastically stretch when the silicon-carbon particles expand, absorbing the expansion stress. The hard segment microphase region acts as a physical cross-linking point to maintain structural integrity, forming a multi-layered bonding network with the carboxyl groups of PAA, thereby inhibiting the overall expansion of the electrode and the shedding of active material. With the silicon-carbon content increased to 15%, Example 7 increased the polyurethane ratio to 2:1, and the expansion rate after 300 cycles was controlled at 20.4%, still significantly better than the 44.7% of Comparative Example 2, indicating that different silicon-carbon loadings can be adapted by adjusting the polyurethane / PAA ratio.
[0067] Example 8 (Electrolyte stability verification) The aqueous polyurethane dispersion prepared in Example 4 was cast into a film with a thickness of approximately 50 μm, dried at 80°C for 4 hours, and then cured at 120°C for 2 hours. The film was then cut into 30 mm × 30 mm samples. The samples were immersed in an electrolyte solution (1 mol / L LiPF6, EC:DEC:DMC = 1:1:1 volume ratio, containing 5 wt% FEC), sealed, and stored at 60°C for 7 days. After removal, residual liquid on the surface was quickly wiped off, the thickness was measured according to GB / T 7125-2014, and the mass was measured using an analytical balance.
[0068] Test results: Before immersion, the average thickness was 50.3 μm and the average mass was 0.045 g; after immersion for 7 days, the average thickness was 53.1 μm and the average mass was 0.058 g. Mass swelling rate = (0.058 - 0.045) / 0.045 × 100% ≈ 28.9%; thickness swelling rate ≈ 5.6%. These data indicate that the polyurethane only undergoes moderate liquid absorption and swelling in the lithium-ion battery electrolyte environment, without dissolving or breaking down, and can be used as a negative electrode binder for long-term survival in the battery cell.
[0069] The principle is that the urethane groups in the polyurethane molecular chain have a certain polarity, and their interaction with the carbonate solvent in the electrolyte is controllable; at the same time, the hard segment microphase region forms a physical cross-linking network due to hydrogen bonding, which restricts the free extension of the polymer chain in the solvent, thereby keeping the swelling rate at a low level.
[0070] The above examples demonstrate the flexible adaptability of the composite binder system of this invention under different silicon-carbon contents and different polyurethane structures. Those skilled in the art can optimize and adjust the silicon-carbon ratio, polyurethane / PAA ratio, and polyurethane soft and hard segment structure within the scope of the claims, according to actual cell design requirements.
[0071] Finally, it should be emphasized that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A silicon-carbon anode composite binder, characterized in that, The adhesive comprises specialty polyurethane and polyacrylic acid; The special polyurethane has a large number of repeating urethane groups (-NH-COO-) on its molecular backbone, and the overall molecular chain exhibits a special block structure with soft and hard segments separated into microphases. The hard segment is composed of urethane segments formed by the reaction of aromatic or aliphatic diisocyanates with small molecule chain extenders, with a large number of hydrogen bonds forming between molecules. The soft segment is a long-chain flexible macromolecular chain of polyether or polyester. Hard segments aggregate with each other due to hydrogen bonding to form microphase regions, which are dispersed in a continuous soft segment matrix, forming a microphase-separated structure.
2. The silicon-carbon anode composite binder according to claim 1, characterized in that, The soft segment of the special polyurethane is a polyether polyol or a polyester polyol. The polyether polyol is selected from one or more of polyethylene oxide ether, polypropylene oxide ether, and polytetrahydrofuran ether. The polyester polyol is selected from one or more of polyethylene adipate, polybutylene adipate, and polycarbonate polyol.
3. The silicon-carbon anode composite binder according to claim 1, characterized in that, The diisocyanate is selected from one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI); the chain extender is selected from one or more of ethylene glycol, 1,4-butanediol, 1,6-hexanediol, ethylenediamine, and diaminodiphenylmethane.
4. The silicon-carbon anode composite binder according to claim 1, characterized in that, The mass ratio of the special polyurethane to PAA is 1:10 to 10:1; preferably 1:5 to 5:
1.
5. The silicon-carbon anode composite binder according to claim 1, characterized in that, The special polyurethane is an aqueous polyurethane, with water as the dispersion medium; the polyacrylic acid is an aqueous polyacrylic acid emulsion or aqueous solution.
6. A negative electrode sheet, characterized in that, The negative electrode sheet includes a current collector and a negative electrode active layer coated on the surface of the current collector. The raw materials for preparing the negative electrode active layer include: Active materials, including graphite and silicon-carbon composites; Conductive agents; and The composite adhesive as described in any one of claims 1 to 5; The special polyurethane in the composite binder buffers the volume expansion of silicon carbon particles during charging and discharging through the elastic deformation of its soft segments, maintains the integrity of the electrode structure through hydrogen bonding aggregation in its hard segment microphase region, and enhances interfacial adhesion through hydrogen bonding between its polar urethane groups and the surface of the active material and the current collector.
7. The negative electrode sheet according to claim 6, characterized in that, The raw material composition for preparing the negative electrode active layer, by mass percentage, is as follows: Active material: 85%–97%, conductive agent: 1%–8%, composite binder: 2%–7%; The total mass of the composite adhesive is the sum of the special polyurethane and polyacrylic acid, with the special polyurethane accounting for 10% to 90% of the total mass of the adhesive.
8. The negative electrode sheet according to claim 6, characterized in that, The silicon-carbon composite material is prepared by chemical vapor deposition, and the total cell capacity of the silicon-carbon composite material is 1000-1800 mAh / g; the total cell capacity of the graphite is 340-360 mAh / g.
9. A lithium-ion battery, characterized in that, The lithium-ion battery includes a positive electrode, a separator, an electrolyte, and a negative electrode as described in any one of claims 6 to 8.
10. A method for preparing a lithium-ion battery as described in claim 9, characterized in that, The method includes the following steps: S1. Active material, conductive agent, special polyurethane and polyacrylic acid are added to deionized water and mixed into a slurry to obtain a uniformly dispersed negative electrode slurry; wherein, the special polyurethane and polyacrylic acid form an interpenetrating network structure in the slurry. S2. The negative electrode slurry is coated onto the surface of the copper foil current collector to form a wet coating. S3. Dry the coated electrode to remove solvent and moisture, so that the special polyurethane and polyacrylic acid can be cured together to form a bonding network between the active materials. S4. Roller-press the dried electrode sheets to control the porosity of the electrode sheets; S5, the rolled electrode sheet is cut and assembled with the positive electrode sheet and separator, and then the lithium-ion battery is obtained after encapsulation and liquid injection; During the charge-discharge cycle, the soft segments of the special polyurethane undergo elastic stretching to buffer the volume expansion stress of the silicon carbon particles, while the hard segment microphase region serves as a physical crosslinking point to maintain the integrity of the electrode structure. Polyacrylic acid forms hydrogen bonds and chemical bonds with the surface of silicon carbon particles through its carboxyl groups, thereby achieving interface anchoring.